PERBANDINGAN KEANEKARAGAMAN JENIS BURUNG ANTARA LAHAN ASLI KEBUN KELAPA SAWIT DAN LAHAN YANG TELAH DITANAMI KELAPA SAWIT - Sitti Ramlah; Yanto Santosa; Nyoto Santoso (Lambung Mangkurat University-Indonesia, 2020)
The expansion of the oil palm plantation establishment has been arousing someaccusation regarding the loss of biodiversity especially on bird diversity. Hence, this study was conducted to compare the bird diversity between oil palm plantation and its origin land cover. The study was conducted on May 2018 in 2 oil palm plantation in the West Sulawesi and its origin land cover around the plantation area. The observation was done twice a day, in the morning and afternoon, with 3 repetitions. The data was then analyzed using richness index, Evenness index and also index similarity to identify the similarities of bird species similarity between land covers. The result show that the highest number of bird species was found in theoil palm plantation of the company 1 which also happen for the evenness and richness indices. While, the similarity index showed the value about 0.42-0.46. Overall, the land cover changes also causing a change in the bird species composition.